Evaluation of the ecological status of Posidonia oceanica meadows along the Calabrian Coasts: A multi-index approach - Faustino Scarcelli; Chiara Spadaro; Annamaria Ienco; Vincenzo Osso; Pietro Giovannelli; Silvestro Greco; Silvia Mazzuca; Amalia Piro (Ecological Indicators)
This study assessed the ecological status of Posidonia oceanica meadows along the Calabrian coast, a region that acts as a geographical barrier between the eastern and western Mediterranenan basins. In doing so, the study addressed a significant gap in our knowledge of this important marine area. Six Special Areas of Conservation (SAC) were monitored along the Tyrrhenian and Ionian coasts, including the transition zone of the Strait of Messina. Using a comprehensive set of indices, the meadows were analysed with a multi-level approach at the population, individual, and community levels. The results revealed notable structural heterogeneity among the sites, while the Posidonia Rapid Easy Index (PREI) indicated good ecological conditions across all sites despite varying levels of environmental pressure. Individual descriptors, however, showed more nuanced patterns, with some sites exhibiting signs of consistent disturbance. Notably, the Reggio Calabria site displayed unique characteristics, such as wider leaf blades and higher epiphyte biomass, suggesting potential anthropogenic eutrophic impacts. Our findings highlight the complex interactions between environmental factors and human activities that influence these ecosystems. Overall, the results underscore the need for a multi-index approach in monitoring programs to provide a more accurate assessment of the health of P. oceanica meadows, crucial for developing effective conservation strategies in the Mediterranean.